Seizure Semiology in Antibody-Associated Autoimmune Encephalitis. Issue 6 (20th November 2022) - Kaaden, Tillman; Madlener, Marie; Angstwurm, Klemens; Bien, Christian G.; Bogarin, Yuri; Doppler, Kathrin; Finke, Alexander; Gerner, Stefan T.; Reimann, Gernot; Häusler, Martin; Handreka, Robert; Hellwig, Kerstin; et al.
Abstract : Background and Objectives: To assess seizure characteristics in antibody (ab)-associated autoimmune encephalitis (ab + AE) with the 3 most prevalent abs against N-methyl-d -aspartate receptor (NMDAR), leucine-rich glioma-inactivated protein 1 (LGI1), and glutamic acid decarboxylase (GAD). Methods: Multicenter nationwide prospective cohort study of the German Network for Research in Autoimmune Encephalitis. Results: Three hundred twenty patients with ab + AE were eligible for analysis: 190 NMDAR+, 89 LGI1+, and 41 GAD+. Seizures were present in 113 (60%) NMDAR+, 69 (78%) LGI1+, and 26 (65%) GAD+ patients and as leading symptoms for diagnosis in 53 (28%) NMDAR+, 47 (53%) LGI+, and 20 (49%) GAD+ patients. Bilateral tonic-clonic seizures occurred with almost equal frequency in NMDAR+ (38/51, 75%) and GAD+ (14/20, 70%) patients, while being less common in LGI1+ patients (27/59, 46%). Focal seizures occurred less frequently in NMDAR+ (67/113; 59%) than in LGI1+ (54/69, 78%) or in GAD+ patients (23/26; 88%). An aura with déjà-vu phenomenon was nearly specific in GAD+ patients (16/20, 80%). Faciobrachial dystonic seizures (FBDS) were uniquely observed in LGI1+ patients (17/59, 29%). Status epilepticus was reported in one-third of NMDAR+ patients, but only rarely in the 2 other groups. The occurrence of seizures was associated with higher disease severity only in NMDAR+ patients. Discussion: Seizures are a frequent and diagnostically relevant symptom of ab + AE. Whereas NMDAR+ patients had few localizing semiological features, semiology in LGI1+ and GAD+ patients pointed toward a predominant temporal seizure onset. FBDS are pathognomonic for LGI1 + AE. Status epilepticus seems to be more frequent in NMDAR + AE.